A escola dos que (não) são: concepções e práticas de uma educação (anti)colonial - Bárbara Bruna Moreira Ramalho (2019)
“In what ways does coloniality is expressed in the education of poor people and how is it questioned, though forbidden, from the resistant existence of these subjects?” This is the guiding question of this thesis. Under the notions of negative and positive recognition of poor students, their place of residence and knowledge, we are concerned with the analysis of “(anti)colonial” school education. Therefore, it is a discussion based on theoretical approaches that denounce the various forms of subordination inscribed in the historical processes of domination of the colonizer over the colonized, the colonialism; but also the persistence of this operation mode even today, the coloniality. Thus, we build our arguments within the scope of this thesis, but we also guide our research, as well as the presentation of the data, in dialogue with authors linked to Latin American critical thinking, post-colonialism, decolonialism, epistemologies of the south and subaltern studies. Looking to achieving the proposed purpose and adopting the Militant Research as a methodological perspective, the study was conducted in a school of the municipal education network of Belo Horizonte, named Anderson Gomes; and in an urban occupation, which was named Marielle Franco, located very close to this institution. In these contexts, participant observations were carried out, adopting as locus of observation, respectively, the pedagogical coordination and the Occupation Daycare, and semistructured interviews were conducted with 26 subjects, grouped as follows: residents (seven), students (six) and educators (13). It is in the destabilization of the prevalent school crisis discourse formulated from the academic failures of the lower classes students that the discussions in this work contribute. Considering the historical and contemporary colonial association of this institution, instead of the reformist discourse, its structural revision is imperative – an understanding that, indelibly, poses the challenge of (anti)colonial unlearning and, thus, of the imagination of “Other” conceptions and practices of school education with poor students.